Hamlet - Shakespeare, William, 1564-1616 (Salt Lake City, UT : Project Gutenberg, 2000)
"Hamlet" by William Shakespeare is a tragedy written between 1599 and 1601. Set in Denmark, the play follows Prince Hamlet as he seeks revenge against his uncle Claudius, who murdered Hamlet's father to seize the throne and marry Hamlet's mother. After encountering his father's ghost, Hamlet feigns madness while plotting vengeance. Considered one of the most powerful tragedies in English literature, this complex tale of betrayal, murder, and moral uncertainty remains endlessly influential. (This is an automatically generated summary.)
There is an improved edition of this title, eBook #100
Wikipedia page about this book: https://en.wikipedia.org/wiki/Hamlet
Release date is 2000-07-01
Keywords: Tragedies (Drama); Hamlet (Legendary character) -- Drama; Kings and rulers -- Succession -- Drama; Murder victims' families -- Drama; Fathers -- Death -- Drama; Revenge -- Drama; Princes -- Drama; Denmark -- Drama